Cellular Response to a Novel Fetal Acellular Collagen Matrix: Implications for Tissue Regeneration - Rennert, Robert C.; Sorkin, Michael; Garg, Ravi K.; Januszyk, Michael; Gurtner, Geoffrey C. (International Journal of Biomaterials, 2013)
Introduction. PriMatrix (TEI Biosciences Inc., Boston, MA, USA) is a novel acellular collagen matrix derived from fetal bovine dermis that is designed for use in partial- and full-thickness wounds. This study analyzes the cellular response to PriMatrix in vivo, as well as the ability of this matrix to facilitate normal tissue regeneration. Methods. Five by five mm squares of rehydrated PriMatrix were implanted in a subcutaneous fashion on the dorsum of wild-type mice. Implant site tissue was harvested for histology, immunohistochemistry (IHC), and flow cytometric analyses at multiple time points until day 28. Results. PriMatrix implants were found to go through a biological progression initiated by a transient infiltrate of inflammatory cells, followed by mesenchymal cell recruitment and vascular development. IHC analysis revealed that the majority of the implanted fetal dermal collagen fibers persisted through day 28 but underwent remodeling and cellular repopulation to form tissue with a density and morphology consistent with healthy dermis. Conclusions. PriMatrix implants undergo progressive in vivo remodeling, facilitating the regeneration of histologically normal tissue through a mild inflammatory and progenitor cell response. Regeneration of normal tissue is especially important in a wound environment, and these findings warrant further investigation of PriMatrix in this setting.